A human monoclonal antibody bivalently binding two different epitopes in streptococcal M protein mediates immune function. Issue 2 (12th December 2022) - Bahnan, Wael; Happonen, Lotta; Khakzad, Hamed; Kumra Ahnlide, Vibha; de Neergaard, Therese; Wrighton, Sebastian; André, Oscar; Bratanis, Eleni; Tang, Di; Hellmark, Thomas; Björck, Lars; Shannon, Oonagh; et al.
Abstract: Group A streptococci have evolved multiple strategies to evade human antibodies, making it challenging to create effective vaccines or antibody treatments. Here, we have generated antibodies derived from the memory B cells of an individual who had successfully cleared a group A streptococcal infection. The antibodies bind with high affinity in the central region of the surface‐bound M protein. Such antibodies are typically non‐opsonic. However, one antibody could effectively promote vital immune functions, including phagocytosis and in vivo protection. Remarkably, this antibody primarily interacts through a bivalent dual‐Fab cis mode, where the Fabs bind to two distinct epitopes in the M protein. The dual‐Fab cis‐binding phenomenon is conserved across different groups of M types. In contrast, other antibodies binding with normal single‐Fab mode to the same region cannot bypass the M protein's virulent effects. A broadly binding, protective monoclonal antibody could be a candidate for anti‐streptococcal therapy. Our findings highlight the concept of dual‐Fab cis binding as a means to access conserved, and normally non‐opsonic regions, regions for protective antibody targeting. Synopsis: Group A streptococci are experts at avoiding and disarming human antibodies with no available vaccines or antibody treatments. This study presents a novel interaction mechanism between antibodies and antigens that can induce protective immune function against group A streptococci. We have generated antibodies from human B cells against streptococcal M protein cross‐reactive across bacterial strains. One antibody can contact its target antigen at two sites in a cis‐bivalent manner, which we term dual‐Fab binding. Comparing antibodies that share epitopes but have single vs. dual‐Fab binding showed that dual‐Fab binding is associated with strongly enhanced immune function. Animal studies show that dual‐Fab antibodies can protect animals against streptococcal disease. Abstract : Group A streptococci are experts at avoiding and disarming human antibodies with no available vaccines or antibody treatments. This study presents a novel interaction mechanism between antibodies and antigens that can induce protective immune function against group A streptococci.